Aaru's Awakening special effects - Marinó Vilhjálmsson 1986- (2013)
Final report. printed copy along with code and other documents are stored in the library at Reykjavík University. Heildartexti lokaskýrslu. Prentuð útgáfa og öll fylgiskjöl á CD eru varðveitt í bókasafni HR. The project is a set of three computer graphic special effects for the 2D platformer video game Aaru’s Awakening, currently being developed by the video game developers at Lumenox. This product will be used by the developers and art director at Lumenox. This can only be run inside the environment it was developed for, which is the Unity3D game development engine. Of those three effects, only two were researched and implemented and though some research was put into the third, there was not enough time to finish and implement it. The two special effects that were implemented are Shadow Cutout and Heat Distortion for full screen background and selected geometry. The third was lighting for the main character’s teleportation projectile. Aaru is the game’s main character, and one of his special abilities is firing a burning projectile that he can then later teleport to where ever it lands. The theory that was cooked up will be explained to some extent in this report to give some idea on how someone could implement it. The architecture of the video game which will use these effects, requires specifically designed effects for various reasons. The game is in 2D as a result the geometry has no way of describing the way it should react to lighting, secondly the art was not created with surface describing maps from the start and testing of some other general solutions had already been fruitless. The methods that were researched are explained in some detail. Graphic programming requires that the result has to look as good as possible for the smallest computing effort possible, and part of the problem is finding the correct scale of good enough and fast enough. Even though these effects were developed for Aaru’s Awakening, they were designed to be loosely coupled and can be used on similarly constructed environments. ...